A change in altitude : a novel - Shreve, Anita (New York : Little, Brown and Co., 2009)
Newlyweds Margaret and Patrick join a climbing expedition to Mount Kenya, and during their harrowing ascent, a horrific accident occurs. In the aftermath of the tragedy, Margaret struggles to understand what happened on the African mountain and how these events have transformed her and her marriage, perhaps forever.
Keywords: Newlyweds -- Fiction; Accidents -- Fiction; Married people -- Fiction; Kenya -- Fiction